Renewable energy development in Malaysia: Communication barriers towards achieving the national renewable energy target - Khairudin N.F.; Bidin R.; Shamsuddin A.H.; Akhiar A.; Ideris F.; Rahman A.A. (Institute of Physics Publishing, 2023)
Renewable energy resources; Communication barriers; Conventional energy sources; Fuel diversification; Malaysia; Malaysians; Renewable energies; Renewable energy development; Sustainable development